Prevalence of frailty and associated factors in Shanghai older community-dwelling adults: a cross-sectional study - Jing Wang; Chuan Chen; Lin Sun; Jiulin Chen; Zhen Qi; Beiling Wu; Dingzhu Shen; Zhihua Yu (BMJ Open)
Objective Frailty is recognised as an emerging public health priority. However, there is still a lack of large-sample, well-designed clinical observational studies investigating frailty status among multidistrict community-dwelling older adults in Shanghai. Therefore, this study aims to establish a large-sample prospective cohort in Shanghai, investigate the frailty status of multidistrict community-dwelling older adults, analyse the characteristics of the frail population and explore potential risk factors for frailty in older adults.Design The present study was a cross-sectional analysis embedded within an ongoing prospective population-based cohort study.Setting and participants A total of 2950 residents (≥65 years) from 9 subdistricts were recruited.Measures We used a stratified cluster random sampling method to obtain a representative sample of older adults in Shanghai. All participants completed paper questionnaires during face-to-face interviews and underwent physical examinations conducted by the investigation team.Results Our results showed that the overall age-standardised prevalence of frailty was 9.91% (95% CI 9.50% to 10.31%). Prevalence was 8.30% (95% CI 6.84% to 9.76%) in men and 9.93% (95% CI 8.85% to 11.01%) in women. Advancing age, female sex, lower education level and comorbidities were significantly associated with frailty among community-dwelling older adults.Conclusions Clinical and public health efforts to reduce the burden of frailty in China should devote greater attention to older women, particularly those with multiple comorbidities, and prioritise community-based frailty screening and prevention initiatives.Trial registration number ChiCTR2000039491.